Characteristics analysis at prefix granularity: A case study in an IPv6 network. (July 2016) - Li, Fuliang; Yang, Jiahai; Wang, Xingwei; Pan, Tian; An, Changqing; Wu, Jianping
Abstract: As IPv6 has much larger address space than IPv4, investigating the characteristics of IPv6 prefixes is of great benefit to understand and manage IPv6 networks. In this paper, (1) we conduct a case study on prefix-level characteristics in IPv6 world. We find that the number of assigned prefixes and the coverage areas are increasing and expanding. Traffic and packet distribution across prefixes are highly skewed. The sizes of active prefixes are relatively stable over time. These results provide experimental basis for routing cache design in IPv6 world. If we update the routing cache once an hour, we only need to reserve 5184 bytes memory for the worst-case burst changes. (2) In addition, we find that 61% destination prefixes have more than two paths to reach, which shows that multihoming path diversity of the studied IPv6 network is obvious. Therefore, we propose an experimental framework with the ability of measuring the performance of each destination prefix, tuning the path for each destination prefix with the best performance, and evaluating the effect during and after the performance tuning. IPv6 has been experiencing fast development as the next generation network. Hence understanding prefix-level characteristics and enhancing performance management are essential for IPv6 networks.